Comparison of Dracocephalum Moldavica Essential Oil with Chlorhexidine on Cariogenic Bacteria - Bahareh NazemiSalman; Seyedeh Solmaz Taheri; Fatemeh Heidari; Alireza Yazdinezhad; Fakhri Haghi; Mahsa Shabouei Jam; Samira Basir Shabestari (Shiraz University of Medical Sciences, 2024)
Statement of the Problem: Dental caries and periodontal disease are the most common oral problems. Chemical antibacterial agents often have side effects; thus, researchers have long been in search for organic and herbal products to prevent dental caries and periodontal disease.Purpose: The present study has aimed to assess the effects of Dracocephalum moldavica essential oil on Streptococcus mutans, Streptococcus salivarius, Streptococcus sobrinus, and Lactobacillus acidophilus compared to Chlorhexidine (CHX).Materials and Method: In this in vitro study, the plants were collected from Zanjan Province, Iran. Analysis of the essential oil was carried out by gas chromatography/mass chromatography. Micro-broth dilution and disc diffusion methods were used for assessment of the antimicrobial activity, and minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) were evaluated.Results: The mean diameter of the growth inhibition zones in the well plate method for Dracocephalum moldavica showed that it had greater antimicrobial activity against Lactobacillus acidophilus than others (p Value= 0.01). Furthermore, Dracocephalum moldavica had higher antimicrobial activity than CHX. The results of MIC and MBC showed that Dracocephalum moldavica had lower antibacterial activity than CHX.Conclusion: Dracocephalum moldavica essential oil demonstrated antibacterial properties against cariogenic bacteria. Given that other favorable properties of these essential oils are confirmed, they may be suitable for use as antibacterial agents in the formulation of oral healthcare products.